2017
DOI: 10.1016/j.surfcoat.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scratch testing of (Ti,Fe)N x thin films on silicon

Abstract: Thin films of (Ti,Fe)Nx have been produced on silicon wafers with a wide range of compositions and mechanical properties to investigate correlations between the mechanical properties measured by indentation and crack resistance in the highly loaded sliding contact in a nano-scratch test. The nano-scratch test data on the thin films using a well-worn Berkovich indenter with ~1 m end radius were supported by high resolution scanning electron microscopic (SEM) imaging and analytical stress modelling. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Coatings with very high H/E can behave poorly due to their limited ductility, with reduced critical load. For hard coatings deposited on silicon there is more extensive delamination at failure [16,17,20,29], or chipping for harder DLC coatings on hardened steel [35]. Consistent with this general trend the smallest critical load was found for the hardest coating, TiAlN.…”
Section: Ramped Load Scratch Testing At 25 ºCsupporting
confidence: 65%
See 2 more Smart Citations
“…Coatings with very high H/E can behave poorly due to their limited ductility, with reduced critical load. For hard coatings deposited on silicon there is more extensive delamination at failure [16,17,20,29], or chipping for harder DLC coatings on hardened steel [35]. Consistent with this general trend the smallest critical load was found for the hardest coating, TiAlN.…”
Section: Ramped Load Scratch Testing At 25 ºCsupporting
confidence: 65%
“…It has been shown previously that a strong correlation exists between the mechanical properties of coatings (primarily hardness and H/E) and the scratch test critical load (L c2 ) [16,17,20,34]. The nanoindentation data in Table 1 shows that at room temperature TiAlN was hardest at around 30 GPa, and AlTiN softest (20 GPa), with a significantly lower elastic modulus than the other two coatings [24,25].…”
Section: Ramped Load Scratch Testing At 25 ºCmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous works have shown that there is a correlation between the scratch test critical load Lc2 and the mechanical properties of the coatings, essentially hardness and the ratio of hardness to elasticity (H/E) [39,40]. The nano-indentation data in Figure 6b, shows that at room temperature, the multilayer coating with a 500 nm interlayer has the lowest hardness with elastic modulus of (502.35 ± 11.42092) GPa, which results in the lowest H/E ratio for this coating.…”
Section: Micro-mechanical Property Analysismentioning
confidence: 99%
“…It is mainly used to determine the adhesion strength and evaluate the failure modes of coatings. The majority of published work in nanoscratch testing area relates to establishing mechanical parameters of various coating/substrate systems [22][23][24][25]. However not a much has been done to characterize the mechanical and tribological properties of reinforced barrier coatings.…”
Section: Sample Preparationmentioning
confidence: 99%